Analisis Kepuasan Masyarakat Terhadap Pelayanan Publik Di Kantor Kecamatan Nanggalo Kota Padang Menggunakan Customer Satisfaction Index Dan Importance Performance Analysis. - Mira Mainerlis Nursyam; Helma Helma (Journal of Mathematics UNP, 2020)
Abstract-. The Nanggalo District Office is one of the offices that provides administrative services in the city of Padang. This Nanggalo District Office has facilities and services provided to the community. However, the services from the Nanggalo District Office have not fulfilled the needs and desires of the peoplen in Padang City. This research goal is ton determine the level ofc Consumer Satisfactionn based on the Customer Satisfaction Index (CSI)n and to determine the importance of each attribute based on Importance Performance Analysisn (IPA).. The data of this study. are primary data where there are 100 questionnaires that will be given directly to people of Nanggalo District who have visited at least 2 times. The result showed thatn overall level of Comsumer Satisfaction of 78% was in the range of value 66%80,99% which indicated that the passenger satisfaction index was the “Satisfied”criterion. Keywords-the nanggalo district office, CSI, IPA